A Syd-1 homologue regulates pre- and postsynaptic maturation in Drosophila. - Owald, D; Fouquet, W; Schmidt, M; Wichmann, C; Mertel, S; Depner, H; Christiansen, F; Zube, C; Quentin, C; Körner, J; Urlaub, H; Mechtler, K; et al. (2010)
Active zones (AZs) are presynaptic membrane domains mediating synaptic vesicle fusion opposite postsynaptic densities (PSDs). At the Drosophila neuromuscular junction, the ELKS family member Bruchpilot (BRP) is essential for dense body formation and functional maturation of AZs. Using a proteomics approach, we identified Drosophila Syd-1 (DSyd-1) as a BRP binding partner. In vivo imaging shows that DSyd-1 arrives early at nascent AZs together with DLiprin-alpha, and both proteins localize to the AZ edge as the AZ matures. Mutants in dsyd-1 form smaller terminals with fewer release sites, and release less neurotransmitter. The remaining AZs are often large and misshapen, and ectopic, electron-dense accumulations of BRP form in boutons and axons. Furthermore, glutamate receptor content at PSDs increases because of excessive DGluRIIA accumulation. The AZ protein DSyd-1 is needed to properly localize DLiprin-alpha at AZs, and seems to control effective nucleation of newly forming AZs together with DLiprin-alpha. DSyd-1 also organizes trans-synaptic signaling to control maturation of PSD composition independently of DLiprin-alpha.